Mock Juror Perceptions of a Male or Female Adult Rape Victim Crying in the Courtroom - Pals, Andrea M. (Violence against women, 2024)
This study investigated the impact of victim crying and gender on perceptions of rape cases. Participants (N = 240, 51.5% male, 48.1% female) completed a 2 (victim crying) × 2 (victim gender) × 2 (participant gender) between-participants design with case judgments (e.g., verdict) as the DVs. Results found that a rape victim crying during testimony increased pro-victim judgments compared to when the victim did not cry, that female mock jurors were more pro-victim than males, but that victim gender was insignificant. Finally, the mediation model found that victim crying increased their credibility, increasing the likelihood of a guilty verdict.